Functionalized mesoporous silica thin films as a tunable nonlinear optical material. Issue 33 (11th August 2017) - Laskowska, Magdalena; Kityk, Iwan; Dulski, Mateusz; Jędryka, Jarosław; Wojciechowski, Artur; Jelonkiewicz, Jerzy; Wojtyniak, Marcin; Laskowski, Łukasz
Abstract : The article is about a novel material for application in optoelectronic devices: mesoporous silica in the form of thin films with vertically aligned channels containing anchored propyl-copper-phosphonate functional groups. Abstract : The article is about a novel material for application in optoelectronic devices: mesoporous silica in the form of thin films with vertically aligned channels containing anchored propyl-copper-phosphonate functional groups. We described a synthesis route and carried out characterization of the structure to obtain its nonlinear optical (NLO) properties (second and third order harmonic generation). A quasi phase transition was found in the material resulting from modification of the functional group content. We also demonstrated that it is possible to modify NLO susceptibilities by tuning the distance between active polar units.